2016
DOI: 10.1017/s0266467416000353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forest and cave proximity on fruit set of tree crops in tropical orchards in Southern Thailand

Abstract: Abstract:Deforestation and forest fragmentation are contributing to declines in crop pollinator populations worldwide. Several studies have examined the impact of forest proximity on plant pollination ecology, but concentrated on single crop species. However, it can be more informative to investigate multiple crop and pollinator species in a community, because different pollinator groups may respond differently to forest distance. We evaluated flower visitor diversity, visitation frequency, and fruit set for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 59 publications
1
30
0
1
Order By: Relevance
“…Large‐sized bees with more than 1‐km foraging ranges were predicted to be more resilient in simplified landscapes such that the relative abundance of resources at small scales may have less influence on their foraging behaviour (Jauker et al ., ) in contrast to small‐sized bees, where resource abundance may limit survival in simplified landscapes (Gathmann & Tscharntke, ; Jauker et al ., ). In south‐east Asia, species of Tetragonula whose size is relatively small, are dominant in less disturbed forest (Ghazoul & McLeish, ; Liow et al ., ; Sritongchuay et al ., ). In the present study, we found few stingless bees (<0.7% of the individuals collected) and this was the case in only five of the 24 sites surveyed, suggesting that many smaller bee species may have been extirpated from our study sites.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Large‐sized bees with more than 1‐km foraging ranges were predicted to be more resilient in simplified landscapes such that the relative abundance of resources at small scales may have less influence on their foraging behaviour (Jauker et al ., ) in contrast to small‐sized bees, where resource abundance may limit survival in simplified landscapes (Gathmann & Tscharntke, ; Jauker et al ., ). In south‐east Asia, species of Tetragonula whose size is relatively small, are dominant in less disturbed forest (Ghazoul & McLeish, ; Liow et al ., ; Sritongchuay et al ., ). In the present study, we found few stingless bees (<0.7% of the individuals collected) and this was the case in only five of the 24 sites surveyed, suggesting that many smaller bee species may have been extirpated from our study sites.…”
Section: Discussionmentioning
confidence: 97%
“…However, mass flowering crops may benefit social honeybees in the landscape by providing food for a large number of larva in colonies (Roubik, ; Westphal et al ., ). Based on personal observations, we also found that flies (order Diptera) were prevalent on mango flowers, consistent with other studies (Singh, ; Dag & Gazit, ; Huda et al ., ; Sritongchuay et al ., ), such that nectar resources may have been significantly reduced for bees by these other visiting insects.…”
Section: Discussionmentioning
confidence: 99%
“…These plant species bloom at night and are known to rely on bats for pollination (Start and Marshall, 1976;Bumrungsri et al, 2008Bumrungsri et al, , 2009Srithongchuay et al, 2008Srithongchuay et al, , 2016Acharya et al, 2015;Stewart and Dudash, 2016b).…”
Section: Plant Study Speciesmentioning
confidence: 99%
“…This bat species is relatively large (53-59 g; Stewart and Dudash, 2016b), has a broad diet and is an important pollinator of many night-blooming plant species (Start and Marshall, 1976;Bumrungsri et al, 2008Bumrungsri et al, , 2009Srithongchuay et al, 2008Srithongchuay et al, , 2016Acharya et al, 2015;Stewart and Dudash, 2016b). Because of its broad diet, E. spelaea potentially transfers heterospecific pollen among bat-pollinated plant species.…”
Section: Bat Study Speciesmentioning
confidence: 99%
“…Several studies have been conducted to examine the effect of forest proximity on plant pollination ecology. The evaluation of flower visitor diversity, frequency, and fruit set for three crop species has been conducted in mixed fruit orchards of rambutan (Nephelium lappaceum L.), durian (Durio zibethinus L.), and mango (Mangifera indica L.) [43] in southern Thailand. This study compared 10 pairs of orchards that are located at <1 km and >7 km away from the forest edge.…”
Section: Pollination For Agricultural Productivity and Ecological Sermentioning
confidence: 99%